Peran Guru Sebagai Penguatan Profil Pelajar Pancasila dalam Kurikulum Merdeka Belajar - Reksa Adya Pribadi; Safna Anggraeni Syahid; Astri Oktaria Putri (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
The profile of Pancasila students as part of the independent learning curriculum in the process of strengthening the Pancasila Student Profile is important for the role of a teacher. The purpose of this study is to determine the role of the teacher as strengthening the Pancasila Student Profile in the Independent Learning Curriculum. The research method used is descriptive qualitative. The data collection techniques used are observation, interviews and documentation. From the results of the research conducted, the role of the teacher is very important because the teacher is not only transferring knowledge but also motivation and character in children. In an effort to strengthen the Pancasila Student Profile, teachers must have the main ability, namely as an example / role model for children. Have a learning plan that focuses on the formation of Pancasila values. Make learning based on the local wisdom approach. Building students' awareness through project-based learning models. making learning interesting and not limited to space, place and time. Learning models that utilize IT developments. Creating a learning evaluation centered on the scientific approach.